Interaction of Ampicillin and Amoxicillin with Mn(2+): A Speciation Study in Aqueous Solution - Foti, Claudia (Molecules, 2020)
A potentiometric and UV spectrophotometric investigation on Mn(2+)-ampicillin and Mn(2+)-amoxicillin systems in NaCl aqueous solution is reported. The potentiometric measurements were carried out under different conditions of temperature (15 ≤ t/°C ≤ 37). The obtained speciation pattern includes two species for both the investigated systems. More in detail, for system containing ampicillin MLH and ML species, for that containing amoxicillin, MLH(2) and MLH ones. The spectrophotometric findings have fully confirmed the results obtained by potentiometry for both the systems, in terms of speciation models as well as the stability constants of the formed species. Enthalpy change values were calculated via the dependence of formation constants of the species on temperature. The sequestering ability of ampicillin and amoxicillin towards Mn(2+) was also evaluated under different conditions of pH and temperature via pL(0.5) empirical parameter (i.e., cologarithm of the ligand concentration required to sequester 50% of the metal ion present in traces).